2016
DOI: 10.1161/hypertensionaha.116.07615
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Salt Intake Is a Determinant of Cardiac Changes After Treatment of Primary Aldosteronism

Abstract: Primary aldosteronism is associated with increased left ventricular (LV) mass independently of blood pressure. Previous studies suggest that elevated aldosterone causes cardiac damage only in the presence of an inappropriate salt status. We examined the relevance of dietary salt intake on cardiac changes in patients with primary aldosteronism before and after treatment. Sixty-five patients with tumoral or idiopathic primary aldosteronism were recruited at a University medical center and followed after either s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 40 publications
2
30
0
2
Order By: Relevance
“…Similarly, in humans, extraordinarily high aldosterone concentrations in populations with chronic sodium deficiency was not associated with cardiovascular damage ( 49 ). A recent study demonstrated that dietary salt intake influenced the reduction of LV mass after PA treatment ( 50 ). Thus, dietary sodium intake may have influenced our results.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in humans, extraordinarily high aldosterone concentrations in populations with chronic sodium deficiency was not associated with cardiovascular damage ( 49 ). A recent study demonstrated that dietary salt intake influenced the reduction of LV mass after PA treatment ( 50 ). Thus, dietary sodium intake may have influenced our results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their data depicted the relationship between the sodium level among PA patients with higher sodium intake (corresponding to the medium and high tertiles in our data) and LV structure. One recent study investigated the association between dietary salt intake and cardiac change after treatment in patients with PA [ 31 ]. The mean urinary sodium level of patients with PA in that study (149 mmol/d) is closer to ours.…”
Section: Discussionmentioning
confidence: 99%
“…In 21 patients with primary aldosteronism, Pimenta et al found that urinary sodium independently predicts left ventricular mass [ 54 ]. More recently, we have shown that an increased left ventricular mass is associated with daily urinary sodium excretion and plasma aldosterone levels in 65 patients with primary aldosteronism [ 55 ]. Also, and most important, we found that the extent of a reduction in left ventricular mass obtained after either surgical or medical treatment of primary aldosteronism was independently correlated with the decrease in urinary sodium observed during treatment.…”
Section: The Contribution Of Salt To Aldosterone-related Cardiac Dmentioning
confidence: 99%